2005
DOI: 10.1152/ajpregu.00418.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gestational programming: population survival effects of drought and famine during pregnancy

Abstract: The process whereby a stimulus or stress at a critical or sensitive period of development has long-term effects is termed "programming." Studies in humans and animals convincingly demonstrate that environmental perturbations in utero may permanently change organ structure and metabolism and/or alter homeostatic regulatory mechanisms among the offspring. These programmed changes may be the origins of adult diseases, including cardiovascular disease, obesity, and diabetes. Throughout evolution and development, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
102
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 80 publications
6
102
2
1
Order By: Relevance
“…The water deprivation following the decreased fluid intake by the HS rats may have caused a state of hypernatremia in these rats (Ross & Desai, 2005) as observed in the present study. Also, aqueous extract of HS has been shown to be rich in Na + (Adigun et al, 2006) suggesting that consumption of aqueous extract of HS increases the body's Na + load.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The water deprivation following the decreased fluid intake by the HS rats may have caused a state of hypernatremia in these rats (Ross & Desai, 2005) as observed in the present study. Also, aqueous extract of HS has been shown to be rich in Na + (Adigun et al, 2006) suggesting that consumption of aqueous extract of HS increases the body's Na + load.…”
Section: Discussionsupporting
confidence: 70%
“…The decreased food consumption in the two groups of HS dams in the present study may have been due to hypernatremia-induced dehydration-anorexia (Ross & Desai, 2005). The hypernatremia observed in the present study in the HS dams may have been due to a 1.07 ± 0.26 0.6 g/100 mL 1.01 ± 0.09* 2.13 ± 0.27* 4.98 ± 0.42 † 2.56 ± 0.88* 1.8 g/100 mL 1.09 ± 0.06* 2.26 ± 0.18* 2.54 ± 0.19 2.90 ± 0.18* PND, Postnatal day; N = 9/group; *, P < 0.05 versus control; † , P < 0.05 versus control and 1.8 g/100 mL.…”
Section: Discussionmentioning
confidence: 52%
“…These observations may therefore suggest that exposure to an aqueous extract of HS during pregnancy decreases pregnancy weight gain and postpartum weight loss through a mechanism not yet fully understood. We, therefore, hypothesize that HS exposure that commenced on day one of pregnancy through PPD 34 in the exposed groups (A and B) may have induced a state of dehydration (water deprivation) in pregnancy, directly or indirectly, in these dams as evidenced by the reduced fluid intake (table 1) which created an osmotic stress (Ross and desai, 2005). Mojiminiyi et al (2000) have shown that consumption of aqueous extract of HS causes hypernatremia possibly through its diuretic action.…”
Section: Discussionmentioning
confidence: 96%
“…Mojiminiyi et al (2000) have shown that consumption of aqueous extract of HS causes hypernatremia possibly through its diuretic action. Water deprivation with the accompanying plasma hypernatremia is associated with dehydrationanorexia (Ross and Desai, 2005). This may have been responsible for the decreased food intake (table 2) and the consequent reduced weight gain (table 3) in the exposed groups.…”
Section: Discussionmentioning
confidence: 99%
“…Suckling of IUGR pups by ad libitum-fed dams induces accelerated catch-up growth, which is related to an increased percentage of body fat in adulthood and high leptin levels [39]. In contrast, preventing early catchup growth in IUGR or small for gestational age (SGA) offspring may diminish the risk of obesity in later life [39,40].…”
Section: Maternal Undernutrition and Accelerated Catch-up Growthmentioning
confidence: 99%